- - Puerto, Juan José (Acta Bioethica, 2000)
Coincidental with a large-scale application of human reproductive biomedical techniques in the middle eighties, the world of Law reacted by setting up rules for these new technologies. Legislation proposed in those years responded to the principle of safeguarding Human Being's fundamental Rights, which by then, were viewed -by the predominant juridical doctrine- from an individualistic perspective with individual social-economic rights (2nd Generation Human Rights ) that overestimated the principle of selfdetermination. All this resulted in laws favouring parents interests over embryo's and future generations' rights. Placed in the nineties, the evolution of political-constitutional thinking has contributed to the development of the future generations' Human Rights (3rd Generation Human Rights), putting an end to previous individualism by taking into consideration new values such as ecologism, respect to nature and its resources, and so forth. The Principle of responsibility as well as the Principle of precaution in the application of brand new technologies will be juridically demanded; principles that justify the existence of a legislation intended to promote a balance between rights and interests of each one of the participants in assisted reproduction treatments (including son-to-be). This shift in the doctrine of fundamental rights translates into practical consequences in a variety of issues related to the regulation of these reproductive techniques ( embryo cryopreservation, germ cells donors, posthumous reproduction, informed consent, and so forth).